Wider Caribbean financial sector review : increasing competitivenes and financial resource management for economic growth - IBRD (Caribbean Group for Cooperation in Economic Development [Washington]US, 1998)
Seeks to demonstrate the common characteristics and constraints of the financial markets and institutions throughout the wider Caribbean and to identify factors which might improve the availability and security of capital needed to find productivee investment in the region.